The Ghostly Grounds: Scandal and Supper (A Canine Casper Cozy Mystery-Book 5) - Sophie, Love (Lukeman Literary, 2021)
"The perfect romance or beach read, with a difference: its enthusiasm and beautiful descriptions offer an unexpected attention to the complexity of not just evolving love, but evolving psyches. It's a delightful recommendation for romance readers looking for a touch more complexity from their romance reads." --Midwest Book Review (For Now and Forever) THE GHOSTLY GROUNDS: SCANDAL AND SUPPER is Book #5 in a charming new cozy mystery series by bestselling author Sophie Love, author of The Inn at Sunset Harbor series, a #1 Bestseller with over 200 five-star reviews! Marie Fortune, 39, a successful dog groomer in Boston, leaves the stressful life behind and heads to a small town in coastal Maine to create a new life. She remains intent on renovating the old, historic house her great-aunt left her and giving it a new life as a B&B. Yet there was one thing she couldn't plan for: the house is haunted. Two things, actually: her great-aunt also left her a dog-and he is far from a typical dog. When Marie is hired to cleanse a unique and massive hotel in a nearby town, the scope of it is beyond anything she has encountered before. Just as she wonders if she has finally met her match, she learns that her local Mayor is trying to re-zone the downtown-and to shut down her B&B while he's at it. Having a murder in the mix-for which she is pinned-hardly helps matters, either. In a multi-front war for her survival, can Marie manage to purge the ghosts, stay out of jail, and keep her livelihood? A page-turning cozy, packed with mystery, love, hauntings, travel, pets and food-anchored around a small town and a B&B in need of renovation that will capture your heart-THE GHOSTLY GROUNDS is an un-putdownable cozy series that will keep you turning pages (and laughing out loud) late into the night. "The romance is there, but not overdosed. Kudos to the author for this amazing start of a series that promises to be very entertaining." --Books and Movies Reviews (For Now and Forever)
Keywords: Krimi, detektivky